2000
DOI: 10.1023/a:1026403805756
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The current dose regimen is administered according to BSA which is the most important factor influencing temozolomide clearance. No further dose adjustment is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…This is consistent with previous studies evaluating the PK profile of oral temozolomide, which demonstrated that temozolomide exhibits linear pharmacokinetics over the therapeutic dose range [2, 4, 1619] and that the PK profile of temozolomide is independent of the route of administration (i.e., intravenous, oral or hepatic intra-arterial infusion) [2]. Other studies have demonstrated that total body clearance of temozolomide is linear [8, 16] and independent of dose [16]. Moreover, the PK characteristics of temozolomide have been shown to be independent of dosing schedules [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with previous studies evaluating the PK profile of oral temozolomide, which demonstrated that temozolomide exhibits linear pharmacokinetics over the therapeutic dose range [2, 4, 1619] and that the PK profile of temozolomide is independent of the route of administration (i.e., intravenous, oral or hepatic intra-arterial infusion) [2]. Other studies have demonstrated that total body clearance of temozolomide is linear [8, 16] and independent of dose [16]. Moreover, the PK characteristics of temozolomide have been shown to be independent of dosing schedules [17].…”
Section: Discussionsupporting
confidence: 90%
“…The key parameter that required optimization was the rate of intravenous infusion so as to better match gastrointestinal absorption kinetics and achieve similar C max values to that achieved via oral administration. Subsequently, Monte Carlo simulations to evaluate virtual crossover exposure equivalence trials using a population PK model derived from a previous population study of oral temozolomide [8] were conducted and suggested that a 90-min intravenous infusion could achieve exposure equivalence with respect to C max (unpublished data). The goal of this pivotal, randomized crossover study was to examine the exposure equivalence and safety profile of a 90-min intravenous infusion of temozolomide compared with an equivalent oral dose.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, intestinal absorption of TEM-CAP might be diminished in patients who have undergone intestinal surgery including small bowel resection, extended mesenteric lymphadenectomy or even pancreatico-duodenectomy. Although the bioavailability of TEM is considered to be > 95%, and its variability is mainly influenced by body surface area, individual variations in pharmacokinetic variables cannot be excluded [41, 42]. The “raw” median OS was similar between the 2 groups (47.05 months with 5FU-DTIC vs. 60.53 months with TEM-CAP, p = 0.24).…”
Section: Discussionmentioning
confidence: 99%
“…i Brandes, Grossman, & Ahmad (2006); Eli Lilly (2013); Ohana, Brahim, & Ibrahim (2016); Rombola et al (2015). j Janus et al (2013); Jen et al (2000); Merck (2008). k Herrington, Figueroa, Kirstein, Zamboni, & Stewart (2001); Novartis (2015); O'Reilly et al (1996).…”
Section: Pemetrexedmentioning
confidence: 99%